2020
DOI: 10.1371/journal.pone.0231431
|View full text |Cite
|
Sign up to set email alerts
|

Dual-source abdominopelvic computed tomography: Comparison of image quality and radiation dose of 80 kVp and 80/150 kVp with tin filter

Abstract: Objective To compare the radiation dose and the objective and subjective image quality of 80 kVp and 80/150 kVp with tin filter (80/Sn150 kVp) computed tomography (CT) in oncology patients. Methods One-hundred-and-forty-five consecutive oncology patients who underwent third-generation dual-source dual-energy CT of the abdomen for evaluation of malignant visceral, peritoneal, extraperitoneal, and bone tumor were retrospectively recruited. Two radiologists independently reviewed each observation in 80 kVp CT and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…In clinical routine, the achievable dose savings heavily depend on the patient cohort and the individual protocol settings. Particularly in comparison with low kV levels, a direct comparison of image quality may show a disadvantage of DECT in terms of image contrast [25]. Additionally, DECT protocols require a change in the radiologist's workflow, as most advantages of dual-energy-based imaging only become evident when reading the associated virtual monoenergetic and/or virtual non-contrast datasets in addition [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical routine, the achievable dose savings heavily depend on the patient cohort and the individual protocol settings. Particularly in comparison with low kV levels, a direct comparison of image quality may show a disadvantage of DECT in terms of image contrast [25]. Additionally, DECT protocols require a change in the radiologist's workflow, as most advantages of dual-energy-based imaging only become evident when reading the associated virtual monoenergetic and/or virtual non-contrast datasets in addition [25].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in comparison with low kV levels, a direct comparison of image quality may show a disadvantage of DECT in terms of image contrast [25]. Additionally, DECT protocols require a change in the radiologist's workflow, as most advantages of dual-energy-based imaging only become evident when reading the associated virtual monoenergetic and/or virtual non-contrast datasets in addition [25]. The extent to which DECT protocols are implemented for clinical staging examinations should be weighed up by the respective radiologist.…”
Section: Discussionmentioning
confidence: 99%
“…Our design was consistent with the opinion proposed by multiple studies that BMI is an essential basis for selecting tube voltage level [ 23 ]. Our results showed that radiation doses in the individualized kVp groups were reduced by 70.61%, 56.72% and 31.87%, respectively, compared with the control groups, which is consistent with the results of Nagayama [ 24 ], and Ren [ 25 ].Choi et al [ 26 ] also showed that 80 kVp CT reduced the radiation dose by 45.2% in oncology patients while showing comparable or superior image quality to that of 80/Sn150 kVp CT for abdominal tumor evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing the objective image quality with SNR and CNR seems rather straightforward. Although, when searching for reliable thresholds, a wide variety of values is found in the literature, all presumed to be of diagnostic image quality, and no clear cut-off values have been established [ 33 37 ]. In addition, previous literature states that both SNR and CNR might not encompass the complete appreciation of image quality [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%